Removal of Entrained Organic Matter in the Copper Electrolyte by Ozonation - Cifuentes-Molina, G (Escola de Minas, 2019)
Organic matter-in-aqueous entrainment is a serious problem in the hydrometal-lurgical extraction of copper from ore. Current inefficiencies, changes in the morphology and orientation of cathode deposit are some of the problems when organic matter is present in the advance electrolyte. In addition, negative effects upon metabolic activity of bioleaching microorganisms are reported due to entrained organic matter in the raffinate electrolyte. In view of these problems, the objective of this study was to evaluate ozonation as an alternative method for the removal of entrained organic matter present in an advanced electrolyte. For this purpose, ozonation during 30 min of synthetic solutions using a bubble glass column reactor at different ozone concentrations, flow rates and temperatures were studied. It was found that the increase in all of these operating parameters is not necessarily associated with an increase of the removal efficiency, and their effects on the mass transfer rate, chemical reaction rate, ozone solubility and contact time play a decisive role in the ozonation process. Thus, the best operating conditions were found at 6.7 wt.%, 1 L min-1 and 27 °C and reached a removal efficiency of 94.5%. This result demonstrated that removal of entrained organic matter in strongly acid solution by ozonation could be an alternative technology. © 2019, Escola de Minas. All rights reserved.
Keywords: Copper; Entrainment; Hydrometallurgy; Organic removal; Ozonation